Intelligent and active food packaging : effect of humidity on pore formation in electrospun PLLA fibers - Zhan, Zihui (2013)
The work reported here falls within the framework of a project that deals with accommodating active foods with the use of a functional layer in a recycled polymer packaginf to adsorb/absorb species of interest. Specifically, this work focuses on (i) the preparation and optimization of the porous functional layer ( a non-woven porous fibrous mat) via electrospinning process and (ii) understanding the conditions that yield pores on the fibers.